Complexity and the Art of Public Policy : Solving Society's Problems from the Bottom Up - Colander, David C.; Kupers, Roland, 1959- (Book collections on Project MUSE., 2014)
Complexity science-made possible by modern analytical and computational advances-is changing the way we think about social systems and social theory. Unfortunately, economists' policy models have not kept up and are stuck in either a market fundamentalist or government control narrative. While these standard narratives are useful in some cases, they are damaging in others, directing thinking away from creative, innovative policy solutions. Complexity and the Art of Public Policy outlines a new, more flexible policy narrative, which envisions society as a complex evolving system that.